Proto2Code: uma ferramenta para geração de código front-end a partir de protótipos de telas - Farias, Mailton Viana (2022)
Front-End developers nowadays have several frameworks and software that help them develop their applications. During software development, some common activities require time and effort from the developers, such as the creation of basic registrations with routines for creating, reading, changing, and deleting data. More specifically, in the case of interface development, a lot of time is invested in the front-end implementation of these systems. Therefore, tools can be used to reduce this effort for developers. This work presents the Proto2Code tool, which can speed up the development process by generating front-end code (HTML and CSS) from interface prototypes. For this, a methodology was adopted which is divided into six steps for the construction of a code generator. To validate this version of the tool, a pilot study was conducted with two web developers who participated, in two stages, in the use of the tool. As a result, we found that the tool helps less experienced developers who use more traditional development tools, depending also on the type of prototype used.